Factors contributing to high blood pressure among adults at Folovhodwe Village in Mutale Municipality, Vhembe District in Limpopo Province, South Africa - Ramaano, Ntovholeni Sylvia (My University, 2013)
The aim of the study was to identify factors contributing to high blood pressure among adults at Folovhodwe village Mutale municipality, Vhembe district, Limpopo Province, South Africa. A cross-sectional descriptive study design was used. From the clinic register, 91 patients who were hypertensive in the year 2010 were identified. Of those 76 were females and 15 were males. All patients were included since the number was not big. Self administered questionnaires were used to collect data. All were followed from their place and complete the questionnaires. They were requested to give consent before participating in the study. Descriptive statistics were used to analyse data. Data were entered into SPSS. Frequency tables were used. The findings indicate that majority of participants do not have enough knowledge on factors contributing to high blood pressure. The results show that the followings contribute to high blood pressure: smoking cigarette, alcohol drinking, social problems, and family history, snoring and overweight. The researcher recommends that awareness campaign and researches on high blood pressure should be conducted on a regular basis including factors contributing to high blood pressure to add knowledge that can help in prevention and good management of high blood pressure. Females should be encouraged to empower themselves in order to live better lives and not depend on their partner for daily living as low socioeconomic contribute to high blood pressure. Community health involvement programmes should be encouraged with regards to how to live good lives including physical fitness.
MPH
Department of Public Health
Keywords: high blood pressure; UCTD; Adults; 616.1320968257; Hypertension -- South Africa -- Limpopo; Blood circulation disorders -- South Africa -- Limpopo